2004
DOI: 10.1124/dmd.104.000059
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO METABOLISM OF MK-0767 [(±)-5-[(2,4-DIOXOTHIAZOLIDIN-5-YL)METHYL]-2-METHOXY-N-[[(4-TRIFLUOROMETHYL)-PHENYL] METHYL]BENZAMIDE], A PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR α/γ AGONIST. II. IDENTIFICATION OF METABOLITES BY LIQUID CHROMATOGRAPHY-TANDEM MASS SPECTROMETRY

Abstract: The in vitro metabolism of MK-0767 [(؎)-5-[(2,4-dioxothiazolidin-5-yl) methyl]-2-methoxy-N-[[(4-trifluoromethyl)-phenyl] methyl]benzamide], a novel 2,4-thiazolidinedione (TZD)-containing peroxisome proliferator-activated receptor ␣/␥ agonist, was studied in rat, dog, monkey, and human liver microsomes and hepatocytes, as well as in recombinant human CYP3A4-containing microsomes. Twenty-two metabolites (some at trace levels) were detected by liquid chromatography-tandem mass spectrometry analysis. All appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…A combination of other MS-based techniques, such as stable isotope labeling, accurate mass measurements, and H/D exchange, may help to further narrow possible metabolite structures. When MS analysis fails to provide the absolute identification of the metabolites, LC-NMR should be considered [64][65][66].…”
Section: Metabolite Characterization In Drug Discovery Settingsmentioning
confidence: 99%
“…A combination of other MS-based techniques, such as stable isotope labeling, accurate mass measurements, and H/D exchange, may help to further narrow possible metabolite structures. When MS analysis fails to provide the absolute identification of the metabolites, LC-NMR should be considered [64][65][66].…”
Section: Metabolite Characterization In Drug Discovery Settingsmentioning
confidence: 99%
“…Moreover, S‐oxidation of the TZD ring of troglitazone21 and MK0767 (V. Reddy et al, in preparation) has been implicated in the ring scission observed to occur enzymatically under oxidative conditions. In nonclinical species and humans, the major metabolism pathway for MK‐0767 is believed to proceed via S‐oxidation followed by TZD cleavage and reduction and further methylation and oxidation 22, 23…”
Section: Resultsmentioning
confidence: 99%
“…7,8 The S-oxidation-based ringopened metabolites were also reported by Liu and co-workers, where they emphasized the formation of these metabolites via oxidative cleavage of the TZD ring by S-oxidation. 9 Reddy et al studied the mechanism of metabolic scission of the TZD ring, highlighting the importance of the initial S-oxidation step. 10 Baughman et al reported the CYP3A4-mediated metabolic activation of PGZ in human and rat liver microsomes and hepatocytes, and stressed various ring-opened reactive intermediates and conjugation with glutathione.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Flosequinan and its sulfone metabolite possess vasodilatation, inotropic, and hemodynamic properties, and are useful in acute heart failure . On the other hand, the S -oxidation of thiazolidinedione ( TZD ) ring in the glitazone class of antidiabetic drugs leads to TZD ring-opening followed by several toxicological consequences. …”
Section: Introductionmentioning
confidence: 99%